Pendekatan Restorative Justice Dalam Penyelesaian Kasus Judi Online Yang Melibatkan Anak di Bawah Umur - Putri Maullita Sari (Criminal Law Section Faculty of Law Universitas Sebelas Maret, 2025)
Abstract: Online gambling involving children is a phenomenon that is increasingly widespread due to advances in technology and ease of internet access. The juvenile criminal justice system in Indonesia prioritizes an approach that is not only oriented towards punishment, but also protection and rehabilitation for children as perpetrators of criminal acts. This article discusses the application of a restorative justice approach in resolving online gambling cases involving children by focusing on the best interests of the child, social restoration, and preventing children from committing similar crimes again.Keywords: Restorative Justice, Online Gambling, Children, Juvenile Criminal Justice System, Diversion, Social Rehabilitation.Abstrak: Judi online yang melibatkan anak merupakan fenomena yang semakin marak akibat kemajuan teknologi dan kemudahan akses internet. Sistem peradilan pidana anak di Indonesia mengutamakan pendekatan yang tidak hanya berorientasi pada hukuman, tetapi juga perlindungan dan rehabilitasi bagi anak sebagai pelaku tindak pidana. Artikel ini membahas penerapan pendekatan restorative justice dalam penyelesaian kasus judi online yang melibatkan anak dengan menitikberatkan pada kepentingan terbaik bagi anak, pemulihan sosial, serta pencegahan agar anak tidak kembali melakukan tindak pidana serupa.Kata Kunci: Restorative Justice, Judi Online, Anak, Sistem Peradilan Pidana Anak, Diversi, Rehabilitasi Sosial.